SwiftUI Covid19 Statistics tracking with REST API & Swift 5 - Kababyan, David (Packt Publishing, 2020)
Find out how to build a COVID-19 statistics tracking app for iOS 13 using SwiftUI and Swift 5.1, RESTful API, and JSON parsing About This Video Set up the project and registering for API Understand all the steps involved in app development with SwiftUI Get one month of free iCONS8 access In Detail SwiftUI COVID-19 Statistics Tracking with REST API & Swift 5 is designed to get you up to speed with building a COVID-19 statistics tracking application. This course takes a pragmatic approach to app building, and shows you how to structure your app development and write clean and readable code that can be understood easily. Starting from scratch, you'll gradually progress to building the entire application with the help of expert guidance and tips, along with assets provided to you by the author. Throughout the course, every line of code is typed and explained to help you grasp the steps easily. By the end of this course, you'll have created an app that you'll be able to publish on the app store.